Tuberculosis associated with Mycobacterium tuberculosis Beijing and non-Beijing genotypes: a clinical and immunological comparison - Sun, Yong-Jiang; Lim, T K; Ong, Adrian Kheng Yeow; Ho, Benjamin Choon Heng; Seah, Geok Teng; Paton, Nicholas I (BMC infectious diseases, 2006)
The Mycobacterium tuberculosis Beijing genotype is biologically different from other genotypes. We aimed to clinically and immunologically compare human tuberculosis caused by Beijing and non-Beijing strains. Pulmonary tuberculosis patients were prospectively enrolled and grouped by their M. tuberculosis genotypes. The clinical features, plasma cytokine levels, and cytokine gene expression levels in peripheral blood mononuclear cells (PBMC) were compared between the patients in Beijing and non-Beijing groups. Patients in the Beijing group were characterized by significantly lower frequency of fever (odds ratio, 0.12, p = 0.008) and pulmonary cavitation (odds ratio, 0.2, p = 0.049). Night sweats were also significantly less frequent by univariate analysis, and the duration of cough prior to diagnosis was longer in Beijing compared to non-Beijing groups (medians, 60 versus 30 days, p = 0.048). The plasma and gene expression levels of interferon (IFN) gamma and interleukin (IL)-18 were similar in the two groups. However, patients in the non-Beijing group had significantly increased IL-4 gene expression (p = 0.018) and lower IFN-gamma : IL-4 cDNA copy number ratios (p = 0.01). Patients with tuberculosis caused by Beijing strains appear to be less symptomatic than those who have disease caused by other strains. Th1 immune responses are similar in patients infected with Beijing and non-Beijing strains, but non-Beijing strains activate more Th2 immune responses compared with Beijing strains, as evidenced by increased IL-4 expression.